2016
DOI: 10.1158/0008-5472.can-15-2564
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Bladder Cancer in a Chinese Cohort Reveals a New Susceptibility Locus at 5q12.3

Abstract: Genome-wide association studies (GWAS) of bladder cancer have identified a number of susceptibility loci in European populations but have yet to uncover the genetic determinants underlying bladder cancer incidence among other ethnicities. Therefore, we performed the first GWAS in a Chinese cohort comprising 3,406 cases of bladder cancer and 4,645 controls. We identified a new susceptibility locus for bladder cancer at 5q12.3, located in the intron of CWC27

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…After filtering, we identified 4 common variants and 11 lowfrequency and rare variants that were significantly associated with bladder cancer risk. In addition, we also genotyped additional 11 SNVs that were in previous reported GWA studies (21). Finally, 26 SNVs were selected for further validation in the additional cohorts.…”
Section: Exome Array Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After filtering, we identified 4 common variants and 11 lowfrequency and rare variants that were significantly associated with bladder cancer risk. In addition, we also genotyped additional 11 SNVs that were in previous reported GWA studies (21). Finally, 26 SNVs were selected for further validation in the additional cohorts.…”
Section: Exome Array Analysismentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified 17 independent loci and single nucleotide variants (SNVs) that contribute to bladder cancer susceptibility in European population [(8-14); Table S1]. Many loci have been replicated in additional studies, and additional new loci found to be, associated with bladder cancer risk in Chinese population (15)(16)(17)(18)(19)(20)(21). GWA studies have been successful in identifying common variants involved in complex trait etiology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to family history, heritable genetic variants associated with BCa have been discovered. For example, more than 20 common single nucleotide polymorphisms have been reported in genome‐wide association studies . Rare germline genetic variants with high penetrance, however, have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Rs2042329 ( CWC27 ) was linked to an increased risk of UBC recurrence (OR = 1.26, 95% CI: 1.10; 1.48); while rs804256, rs4639, and rs804276, all located in/close to NEIL2 were associated with NMIBC-only recurrence (OR = 1.23, 95% CI: 1.05–1.43; OR = 1.20, 95%CI: 1.03–1.39; OR = 1.17, 95% CI: 1.01–1.36, respectively). All SNPs that were associated with recurrence showed consistent direction, but were more modest in comparison to the original studies [HR = 1.54 (1.10–2.16) for rs2042329 (12), HR = 4.58 (2.61–8.02) for rs804256 (13), HR = 2.60 (1.68–4.03) for rs4639 (13), and HR = 2.71 (1.75–4.20) for rs804276 (13)].…”
Section: Resultsmentioning
confidence: 85%